HDL-cholesterol confers sensitivity of immunotherapy in nasopharyngeal carcinoma via remodeling tumor-associated macrophages towards the M1 phenotype - Yan Huang; Li Zhang; Ting Yang; Hongyun Zhao; Yunpeng Yang; Ting Zhou; Jianhua Zhan; Xue Bai; Fan Luo; Qun Chen; Wenjuan Ma; Jiaxin Cao; et al. (Journal for ImmunoTherapy of Cancer)
Background The sustained effectiveness of anti-programmed cell death protein-1/programmed death-ligand 1 treatment is limited to a subgroup of patients with advanced nasopharyngeal carcinoma (NPC), and the specific biomarker determining the response to immunotherapy in NPC remains uncertain.Methods We assessed the associations between pre-immunotherapy and post-immunotherapy serum lipoproteins and survival in a training cohort (N=160) and corroborated these findings in a validation cohort (N=100). Animal studies were performed to explore the underlying mechanisms. Additionally, the relationship between high-density lipoprotein-cholesterol (HDL-C) levels and M1/M2-like macrophages, as well as activated CD8+T cells in tumor tissues from patients with NPC who received immunotherapy, was investigated.Results The lipoproteins cholesterol, HDL-C, low-density lipoprotein-cholesterol, triglycerides, apolipoprotein A-1 (ApoA1), and apolipoprotein B, were significantly altered after immunotherapy. Patients with higher baseline HDL-C or ApoA1, or those with increased HDL-C or ApoA1 after immunotherapy had longer progression-free survival, a finding verified in the validation cohort (p<0.05). Multivariate analysis revealed that baseline HDL-C and elevated HDL-C post-immunotherapy were independent predictors of superior PFS (p<0.05). Furthermore, we discovered that L-4F, an ApoA1 mimetic, could inhibit tumor growth in NPC xenografts. This effect was associated with L-4F’s ability to polarize M2-like macrophages towards an M1-like phenotype via the activation of mitogen-activated protein kinase (MAPK) p38 and nuclear factor-κB (NF-κB) p65, thereby alleviating immunosuppression in the tumor microenvironment. Importantly, in patients with NPC with high plasma HDL-C levels, the number of M2-like macrophages was significantly decreased, while M1-like macrophages and activated CD8+T cells were notably increased in those with high HDL-C levels.Conclusion Higher baseline HDL-C levels or an increase in HDL-C post-immunotherapy can enhance immunotherapeutic responses in patients with NPC by reprogramming M2-like macrophages towards the M1 phenotype. This suggests a potential role for prospectively exploring ApoA1 mimetics as adjuvant agents in combination with immunotherapy.